x+16-x+34=-1

To write x+16 as a fraction with a common denominator, multiply by 22.

x+16⋅22-x+34=-1

To write -x+34 as a fraction with a common denominator, multiply by 33.

x+16⋅22-x+34⋅33=-1

Write each expression with a common denominator of 12, by multiplying each by an appropriate factor of 1.

Multiply x+16 and 22.

(x+1)⋅26⋅2-x+34⋅33=-1

Multiply 6 by 2.

(x+1)⋅212-x+34⋅33=-1

Multiply x+34 and 33.

(x+1)⋅212-(x+3)⋅34⋅3=-1

Multiply 4 by 3.

(x+1)⋅212-(x+3)⋅312=-1

(x+1)⋅212-(x+3)⋅312=-1

Combine the numerators over the common denominator.

(x+1)⋅2-(x+3)⋅312=-1

Rewrite (x+1)⋅2-(x+3)⋅312 in a factored form.

Apply the distributive property.

x⋅2+1⋅2-(x+3)⋅312=-1

Move 2 to the left of x.

2⋅x+1⋅2-(x+3)⋅312=-1

Multiply 2 by 1.

2x+2-(x+3)⋅312=-1

Apply the distributive property.

2x+2+(-x-1⋅3)⋅312=-1

Multiply -1 by 3.

2x+2+(-x-3)⋅312=-1

Apply the distributive property.

2x+2-x⋅3-3⋅312=-1

Multiply 3 by -1.

2x+2-3x-3⋅312=-1

Multiply -3 by 3.

2x+2-3x-912=-1

Subtract 3x from 2x.

-x+2-912=-1

Subtract 9 from 2.

-x-712=-1

-x-712=-1

-x-712=-1

Multiply both sides of the equation by 12.

-x-7=-1⋅12

Remove parentheses.

-x-7=-1⋅12

Multiply -1 by 12.

-x-7=-12

Move all terms not containing x to the right side of the equation.

Add 7 to both sides of the equation.

-x=-12+7

Add -12 and 7.

-x=-5

-x=-5

Multiply each term in -x=-5 by -1

Multiply each term in -x=-5 by -1.

(-x)⋅-1=(-5)⋅-1

Multiply (-x)⋅-1.

Multiply -1 by -1.

1x=(-5)⋅-1

Multiply x by 1.

x=(-5)⋅-1

x=(-5)⋅-1

Multiply -5 by -1.

x=5

x=5

x=5

Solve for x (x+1)/6-(x+3)/4=-1